ANALYSIS OF THE USE OF POSPAY SERVICES ON INCOME LEVEL OF PT. POS INDONESIA (Universitas Dr. Soetomo, 2022)
Pospay is a smartphone application with Android and iOS systems that is provided to the public as a digital channel to access Giro Pos services and other financial transaction services independently. Pospay can also be interpreted as a finance and technology service created by PT. Pos Indonesia by using the Online Payment Point System (SOPP) which aims to make it easier for people to make payments. This study aims to analyze and prove the effect of using pospay services on the level of income at PT. Pos Indonesia. The hypothesis in this study is that there is a significant effect between the use of Pospay Services on the Income Level of PT. Pos Indonesia. In this study, the population used is the customers of the Surabaya Post Office 60000 who use the Pospay Application with a total of approximately 8,380 people. Meanwhile, the sample in this study were 60000 Surabaya Post Office customers who used the Pospay Application. Instrument testing is done by using a questionnaire, the questionnaire must meet the valid and reliable requirements. To find out whether the data generated from the questionnaire measuring instrument can guarantee the quality of the research so that conclusions about the relationships between variables can be trusted, accurate, and reliable so that the research can be accepted, validity and reliability tests are carried out. Data collection techniques were carried out by making observations at the Surabaya Post Office 60000 and also in the form of a questionnaire (questionnaire) distributed to respondents, namely post office customers who use the pospay service application. This study uses a quantitative descriptive approach. The results showed that there was a significant effect between the use of Pospay services on the income level of PT. Pos Indonesia. The conclusion of this study is that if the pospay service is improved, it will further increase the income of PT. Pos Indonesia